Analisis Rekayasa Nilai Lampu Hias dalam Usaha Pengembangan Produk - Muhammad Yusuf; Cyrilla Indri Parwati; Amelia Rachmi Nasution (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Currently, the sales of decorative lighting products are very low because the design of decorative lights are less attractive to consumers. Therefore, the company must develop the product to produce quality products that are updated and attractive to consumers. This research aims to develop the decorative light products using value engineering. Value engineering was used to increase benefits withoutt increasing costs, reducing costs without reducing benefits, or a combination of both. This research was conducted to find out the level of efficiency that can be achieved from several recommended alternatives. Research results showed that the value of the initial design (Product A) was 3,48 x 10-7; product B was 3,16 x 10-7; and product C was 8,83 x 10-7. The use of raw materials has also changed from its initial design which was using a mixture of copper and brass with a thickness of 0,8 mm to an alternative design by using a mixture of copper and brass with a thickness of 0,5 mm. In addition, the study showed that product C are more preferable for consumers. Keywords: decorative lighting, product development, pairwise comparison, value engineering